Social biology of Augochlora (Augochlora) phoemonoe (Hymenoptera, Halictidae) reared in laboratory nests - Dalmazzo, Maria de Los Milagros (2015)
Species of the subgenus Augochlora have been considered solitary, and their behavior was postulated as a reversal from the social condition known for its closest relatives. In this study conclusive evidence of eusocial behavior in the wood-dwelling subgenus Augochlora is presented. Direct observation of behavior within artificial nests in the laboratory allowed to study the suite of behaviors that characterize social structure in the species Augochlora (Augochlora) phoemonoe. The following behaviors were recorded and analyzed: locomotion, feeding, construction activities within the nest, pollen collecting, guarding, oviposition, sudden retreats, antennation-tarsation, passing, and following. The last three behaviors represented interactions between nestmates. Social behavior in this temperate South American species is characterized by: a solitary nest initiation phase, followed by an eusocial phase with at least two broods; the small size of the colonies, with 1-3 first-brood females during the summer foraging period; the long-lived foundresses, alive until the end of the season; lack of morphological differentiation between dominant and subordinate individuals, evidenced by size only, but strong physiological differentiation, with a high reproductive skew; short egg-to-adult developmental time (approximately 30 days); and delayed male production to the second or subsequent broods. Indexes of division of labor ranged between 0.32 and 0.76 for the studied nests, indicating behavioral specialization between colony members. During the eusocial phase daughter bees had the highest frequencies of construction, pollen collection and guarding. Colony integration was mediated by high rates of social interactions, initiated by the foundress.